Rearranging the figures on the tapestry: what Japanese direct translation of European texts can tell us about kanbun kundoku. - Fraleigh, Matthew (Japan Forum, 2019)
From the earliest stages of reading and writing in the Japanese archipelago, the methodology of kanbun kundoku (vernacular reading of literary Sinitic) has been an important means of engagement with Chinese texts. The kanbun kundoku process of glossing and syntactic rearrangement transforms a literary Sinitic source text into a kind of 'translationese' that preserves as closely as possible the diction and structure of the original while making it accessible to readers who may have little or no competence in spoken varieties of Chinese. Yet whether this process should be understood as fundamentally a form of translation is a matter of debate among scholars. In this article, I argue that looking at the early modern phenomenon of ōbun kundoku, by which Japanese scholars applied kundoku methodology to European languages (including Latin, Portuguese, Dutch and English), can offer a valuable perspective. These forms of direct translation are an important although comparatively under-studied aspect of Japanese encounters with European texts and they offer an instructive perspective on kanbun kundoku: the longstanding Japanese method of engagement with foreign-language texts that was their inspiration. The theoretical writings of Japan's early modern scholars of Dutch unmistakably acknowledge a basic commonality between these two forms of kundoku while also clarifying the ways in which the application of kundoku to European languages was distinct from application to literary Sinitic.